Estimation of Subsurface Structure Using Euler Deconvolution Method of Magnetic Data at the Geothermal Area of Sonai Village and its Surroundings, Konawe Regency - Sariani, Sariani; Manan, Abdul; Bahdad, Bahdad; Chahyani, Rani (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
It has been carried out research with the aim of determining the subsurface structure at the geothermal area of Sonai Village and its surroundings, Konawe Regency. The data used are magnetic data obtained through field measurements at 126 points in the N180oS direction. After the data were subjected to diurnal and IGRF corrections, a residual (local) magnetic field anomaly of around -150 nT to 90 nT was obtained. On the residual magnetic anomaly map which has been reduced to the Pole (RTP), the Euler Deconvolution (ED) method is applied to the Index Structure N=0 to estimate the subsurface structure in the form of the presence of minor faults, and it is known that there are 5 minor faults at a depth of around 9 to 38 meters. Information on the existence of these faults is then used in 2D modeling. Modeling results show that these minor faults cut through two rock layers, which are the layers composed of conglomerate rocks from the Alangga Formation and peridotites as bedrock from the Ultramafic Complex. One of the minor faults closest to the manifestation area (hot spring) is at coordinates around 4o1’12.412” S and 122o7’24.263” E to 4o1’15.532” S and 122o7’19.561” E with a distance of ±15 meters. The existence of these minor faults is thought to be the migration routes for heat flow or conduction to the surface at the geothermal area of Sonai Village and its surroundings.